A strategic analysis of the various reforms of Khadi and Village Industries Commission: case-based approach. (1st January 2014) - Deb, Madhurima
The main objective of the study is to critically analyse various reforms of Khadi. Case-based approach is employed and information is collected both from primary and secondary sources. Empirical evidence suggests that though KVIC had noble cause behind its inception, i.e., self-reliant still due to its long organisational structure, lack of market-based approach and too much dependency on the commission it could not achieve its objectives. This study would be helpful for the decision makers in the public sector as they would get insights about the anomalies in the industry and find suitable market and customer focused approach to which will enable them to strengthen their positioning strategies in the future. Academician would find it beneficial as the case study applies some of the notable theories of services marketing to improve the positioning of KVIC outlets. There are very few studies investigating the status of some of the old but potential industries of India and KVIC being one among them.